Near-infrared spectroscopy in newborns and infants under general anesthesia - Šuškevičienė, Ilona; ČeslavaRugytė, Danguolė; Bukauskas, Tomas; Vilkė, Alina; Bilskienė, Diana; Macas, Andrius (Acta medica Lituanica, 2012)
The aim of this study was to find out absolute values of cerebral oxygenation during uncomplicated anesthesia in otherwise healthy newborns and infants undergoing general surgery and to correlate them with demographic and clinical variables. We examined 10 term newborns and infants ASA class I or II without any documented neurological and cardiovascular disorders. All patients underwent general anesthesia with sevoflurane, fentanyl and muscle relaxants. After induction of anesthesia, near-infrared spectroscopy (NIRS) was started and used throughout the surgery. Overall mean (standard deviation (sd)) rSO2 value was 84 ± 8% and weakly correlated with weight (r = 0.5), postnatal age (r = 0.2), SpO2 (r = 0.3) and arterial blood pressure (r = 0.2), p